THE RELATIONSHIP BETWEEN STUDY HABIT AND SELF-CONFIDENCE WITH LEARNING RESULTS OF MATHEMATICS STUDENTS CLASS VII MTs - Ela Nurdiana; Siti Nur Rohmah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
This study aims to determine whether there is a positive and significant relationship between study habits and self-confidence with learning results of mathematics students class VII State Islamic Junior High School (MTs Negeri) 4 Bantul, even semester academic year 2017/2018. This research is quantitative. The population in this study is students class VII MTs Negeri 4 Bantul even semester academic year of 2017/2018, which consists of class VII-A, VII-B, VII-C, VII-D, VII-E, VII-F, VII-G, and VII-H that are totaled at 228 students and sampling using random sampling technique to class obtained class VII-C. The data collection technique is questionnaires, and that technique is used to obtain data on study habits and self-confidence, and test methods are used to obtain the data from math scores. Instruments of test: validity, linearity, and reliability test. Analysis prerequisite test, including the normality test, linearity test, and the test of independence. Data analysis is using product-moment and multiple linear regression analysis. The results showed a positive and significant relationship between study habits and self-confidence with learning results of mathematics students class VII MTs Negeri 4 Bantul even semester academic year of 2017/2018. This is indicated by Fcount  Ftable is > with R =    and R2 =   by SR = % and RC = %, EC =   and EC = %.